Globalization Images in the Umayyad Feminist Poetry (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to prove and mark the birth of a conception revolves around the nonstop attempts of the Umayyad women searching for self-evolution and enlightenment. This conception almost has an initial role in modelling human mind and can be realized in the globalization image of the feminist Umayyad poetry. These images intent to express human needs and place cods of conducts that visualize, defined and generalize the social and human perspective of life. Therefore, these most reasonable and mature images seemed to have the main role in reshaping the image of the universal human. The globalization images could occupied a large dramatic scope as a rich artistic tool that contribute in establishing human personality that is capable to adopt coexistence as a model for living. Moreover, these images prove the leadership and achievement merits that the Umayyad woman was empowered with. These, in turns, could establish and verify an equilibrated world based on the imagination of the Arabic woman in the Umayyad era.